Current Management of Obesity in an Infertile Female-Recent Advances and Future Prospective Drugs - Kulvinder Kochar Kaur,; Gautam Allahbadia ,; Mandeep Singh, (Journal of Pharmacy and Nutrition Sciences, 2013)
With obesity having grown to epidemic proportions, nearly half of women of reproductive age are overweight and obese and this is a major public health problem. Due to unfavourable ovarian stimulation protocols, higher gonadotropin consumption and poor results most insurance companies are reluctant to sponsor treatment for such patients .Since diet and exercise are inadequate treatments and bariatric surgery maybe too extreme, treatment in the model of other chronic diseases by combination therapies has prompted the development of novel combination therapies like Qysmia (topiramate/phentermine)/Contrave (Bupropion SR/Naltrexone SR) which simultaneously target multiple physiological pathways that regulate energy homeostasis to overwhelm endogenous compensatory mechanisms as opposed touse of monotherapies to maintain weight loss. The only concern is the slight risk of teratogenicity with topiramate hence it is better to use contraception while using topiramate/bupropionSR/naltrexoneSR. In obese diabetics the GLP-1 receptor agonists like exenatide/liraglutide remain the drugs of choice incombination with insulin, while combination of lixisenatide and insulinglargine are in the pipeline for the future.